Fixed Asset Revaluation Motivations Les Motivations De Revaluation Des Immobilisation - BENYAMINA, Fatima Zohra; ATIG, Toufik (Finance and Business Economies Review, 2019)
The purpose of our research is to highlight, by means of case study, potential motivations that can be behind asset revaluation. The results from this study indicate that the motivation that can be behind the revaluation decision is to convey a faithful image of the company situation to different stakeholder. Improving borrowing capacity, management opportunism and political costs are not fond to influence the revaluation decision of this company.